2023
DOI: 10.3390/children10091536
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Torsion in Children with Horizontal Strabismus or Orthophoria

Nayrouz Bdeer,
Noa Hadar,
Doris Raveh
et al.

Abstract: Purpose: To report the rate of ocular torsion in children with horizontal strabismus or orthophoria. Methods: A retrospective study design was used. Nineteen children were included in the study, including seven girls, aged 4–16 years. All patients were examined for strabismus and 12 were scheduled for surgical intervention. All participants had digital fundus photos (DRSplus, Padova, Italy) of both eyes at presentation, and 5 of 12 also had fundus photos following the strabismus operation. Patient files were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…Considering that our study excluded patients with oblique muscle paralysis and A/V patterns, we speculate that the tension imbalance described by Shin et al 8 may primarily affect the torsional movement of the eyeball, but has not yet reached the severity to cause muscle paralysis or vertical movement disorders. This is consistent with the findings of Bdeer et al 21 , who observed that in the presence of inferior oblique overaction, ocular torsion was common in children with horizontal strabismus, even without V pattern. On the other hand, Deng et al 22 found that more than 20% of subjects had ocular torsion without accompanying oblique muscle dysfunction, suggesting that ocular torsion may not solely stem from oblique muscle abnormalities.…”
Section: Discussionsupporting
confidence: 93%
“…Considering that our study excluded patients with oblique muscle paralysis and A/V patterns, we speculate that the tension imbalance described by Shin et al 8 may primarily affect the torsional movement of the eyeball, but has not yet reached the severity to cause muscle paralysis or vertical movement disorders. This is consistent with the findings of Bdeer et al 21 , who observed that in the presence of inferior oblique overaction, ocular torsion was common in children with horizontal strabismus, even without V pattern. On the other hand, Deng et al 22 found that more than 20% of subjects had ocular torsion without accompanying oblique muscle dysfunction, suggesting that ocular torsion may not solely stem from oblique muscle abnormalities.…”
Section: Discussionsupporting
confidence: 93%